Analisis Kesiapan Kerja Siswa Sekolah Menengah Kejuruan: Program Keahlian Teknik Pendingin dan Tata Udara - Tipal Surya Muhammad; Riki Mukhaiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research aims to describe the work readiness of students majoring in refrigeration and air conditioning engineering at SMK Negeri 1 West Sumatra. Work readiness is the overall condition of an individual which includes physical, mental and experience life, as well as the willingness and ability to carry out work or an activity. The research method used in this research is a descriptive research method with a quantitative approach. The variable studied was the work readiness of students in the Refrigeration and Air Conditioning Engineering skills program at SMK Negeri 1 West Sumatra. The research instrument used in this research is a questionnaire distributed to respondents directly which has 1 variable and 7 indicators. This research questionnaire was conducted on class The results of this research can be concluded that the work readiness of students majoring in Refrigeration and Air Conditioning Engineering at SMK Negeri 1 West Sumatra is categorized as quite good.